Discovering Women's History: A Practical Manual - Parr, Joy (Labour / Le Travail, 1985)
This article reviews the book, "Discovering Women's History: A Practical Manual," by Deirdre Beddoe.
Keywords: DOCHERTY, Charles; Nonfiction; REVIEWS; STEEL & Steelworkers: The Sons of Vulcan (Book); Steel industry; books